2017
DOI: 10.1155/2017/5792621
|View full text |Cite
|
Sign up to set email alerts
|

Sertraline Induces Toxicity and Behavioral Alterations in Planarians

Abstract: Toxicity attributed to sertraline has been demonstrated recently in different cell types and also in some organisms. We investigated the effect of sertraline on planarians, which are considered suitable for investigations in neurotoxicology and currently are widely used as an animal model in neuropharmacological studies. Planarians treated with 10 µM sertraline showed a rapid reduction in their spontaneous movement until they became completely motionless and then showed a series of asynchronous paroxysms (seiz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 45 publications
(65 reference statements)
0
4
0
Order By: Relevance
“…Decreases in motility have been found in adult flatworms acutely exposed to MDL-12,330A (Matsuyama et al 2004), mianserin (Currie and Pearson 2013;Talbot et al 2014;Chan et al 2016;Shettigar et al 2021), sertraline (Thumé and Frizzo 2017;Weeks et al 2018), and high concentrations of caffeine (Best and Morita 1982;Moustakas et al 2015). Previous studies on the effects of caffeine in planarians have only found behavioral effects at much higher concentrations than we tested here (mM instead of µM).…”
Section: Hts Can Recapitulate Findings From Low-throughput Studiesmentioning
confidence: 57%
See 1 more Smart Citation
“…Decreases in motility have been found in adult flatworms acutely exposed to MDL-12,330A (Matsuyama et al 2004), mianserin (Currie and Pearson 2013;Talbot et al 2014;Chan et al 2016;Shettigar et al 2021), sertraline (Thumé and Frizzo 2017;Weeks et al 2018), and high concentrations of caffeine (Best and Morita 1982;Moustakas et al 2015). Previous studies on the effects of caffeine in planarians have only found behavioral effects at much higher concentrations than we tested here (mM instead of µM).…”
Section: Hts Can Recapitulate Findings From Low-throughput Studiesmentioning
confidence: 57%
“…Acute to short-term exposure to sertraline has been reported to cause many morphological effects, including degeneration in the parasitic flatworm S. mansoni (Weeks et al 2018) and induction of seizures, c-shapes, and screw-like hyperkinesia at low concentrations (1 µM-10 µM) in the freshwater planarian Dugesia tigrina (Thumé and Frizzo 2017), with 10 µM causing lesions and death in D. tigrina at 72 hours. We also observed death at 10 µM in both adult and regenerating planarians but did not observe any significant changes in morphology.…”
Section: Hts Can Recapitulate Findings From Low-throughput Studiesmentioning
confidence: 99%
“…in the freshwater planarian Dugesia tigrina (Thumé and Frizzo 2017), with 10 µM causing lesions and death in D. tigrina at 72 hours. We also observed death at 10 µM in both adult and regenerating planarians but did not observe any significant changes in morphology.…”
Section: Hts Can Recapitulate Findings From Low-throughput Studiesmentioning
confidence: 99%
“…Sertraline was seen to possibly alter brain structures, including the hippocampus and anterior cingulated, in depressed or non-depressed monkeys ( Willard et al, 2015 ). Morever, sertraline is toxic and causes behavioral alterations in planarian which serves as an alternative model for the study of neurotoxicity ( Hagstrom et al, 2015 ; Thume and Frizzo, 2017 ). However, several experimental studies using transgenic AD mouse model ( Nelson et al, 2007 ) or investigating human participants ( Cirrito et al, 2011 ) have been published, showing the potential of antidepressants in ameliorating β-amyloid pathology, while some indicate no significant effect ( Severino et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%